Effect of Composition and Sintering Temperature in the Production of Clay-POFA Ceramic - ABDUL RAZAK, NUR SYAHIRAH (Enhanced Knowledge in Sciences and Technology, 2023)
Palm oil fuel ash (POFA) has the potential to replace quartz in the composition of porcelain because of its distinct properties, such as high silica and hydroxyl group concentrations. This study investigated the effect of composition and sintering temperature under different treated POFA (TPOFA) on the morphology, physical, and mechanical properties of clay-POFA ceramic. The POFA was treated at temperatures of 800 °C, 900 °C, and 1000 °C. The TPOFA was mixed with clay at a composition of 10 wt% to 50 wt% and dry pressed into pellets at a mould pressure of 3 tonnes and sintered at 1100 °C and 1125 °C for 1 hour soaking time respectively. The sintered samples were evaluated the mass loss, volume shrinkage, bulk density, and compressive strength and characterized the surface morphology. The results showed that heat treatment and sintering temperature were crucial, affecting porcelain’s physical and mechanical properties. The highest compressive strength, bulk density, and mass loss were achieved at a sintering temperature of 1125 °C using a treated sample of 900 °C of 10 wt% with the values 313 MPa, and 2.529 g/cm3, respectively. Treated POFA is a good candidate for quartz replacement, and 1125 °C was the best sintering temperature.